Leadership gold lessons learned from a lifetime of leading - Maxwell, John C. (Thomas Nelson, 2008)
A leader among leaders, John Maxwell promised himself early in his career that he wouldn't write this book until he was sixty. And now it's finally here. Leadership Gold took Maxwell a lifetime to write, and it delivers his most valuable lessons from forty years of leading. With his signature style, Maxwell comes alongside like a mentor, candidly taking readers through what feels like a one-on-one leadership program. Leadership Gold offers the best of the best, the tried-and-true lessons that no one but Maxwell can share.